Effect of Hydrogen on the Deformation Development in Titanium Alloy of the Ti-Al-V System under Creep - Grabovetskaya G. P.; Zabudchenko O. V.; Stepanova E. N. Ekaterina Nikolaevna; Mishin I. P. (2017, 2017)
Title screen